Differences in gait performance, quadriceps strength, and physical activity between fallers and nonfallers in women with osteoporosis - Stief, Felix; Kirchner, Marietta (Journal of aging and physical activity, 2016)
The present study should reveal differences in gait performance, quadriceps strength, and physical activity (PA) between fallers and nonfallers in women with osteoporosis. Forty-one women with osteoporosis (17 fallers, 24 nonfallers) participated. Gait analysis shows that fallers were walking with a slower walking speed (−9%, p = .033) and had a shorter stride length (−7%, p = .039). Moreover, fallers showed a decreased ankle power generation (−18%, p = .045). The quadriceps strength was decreased by 24% for fallers (p = .005) while PA showed no significant differences. Although a decrease in ankle power generation could have an effect on floor clearance for limb advancement in the swing phase, the causal relationship between spatiotemporal parameters (walking speed, stride length) and walking ankle joint power generation remains unknown and warrants further investigation. In conclusion, walking speed, stride length, ankle power generation, and quadriceps strength can be used to differentiate between fallers and nonfallers in women with osteoporosis.
Gesehen am 06.02.2019